The Superficial Dermis May Initiate Keloid Formation: Histological Analysis of the Keloid Dermis at Different Depths - Jiao, Hu; Zhang, Tiran; Fan, Jincai; Xiao, Ran (Frontiers in Physiology, 2017)
Several studies have reported on certain aspects of the characteristics of different sites within a keloid lesion, but detailed studies on the keloid dermis at different depths within a keloid lesion are scarce. The aim of this study was to investigate the histology of the keloid dermis at different depths. This study included 19 keloid tissue samples that were collected from 19 patients and 19 normal skin samples, which were harvested from subjects without keloids or hypertrophic scar. Samples were studied by light microscopy using routine hematoxylin and eosin histochemical staining, and immunohistochemistry to detect CD20-positive B-lymphocytes and CD3-positive T-lymphocytes. Sirius Red histochemical staining was used to determine the type of collagen in keloid tissue and normal skin samples. The migratory properties of fibroblasts within the keloid dermis at different depths was compared, using an in vitro migration assay. The findings of this study showed that although the papillary and reticular dermis could be clearly distinguished in normal skin, three tissue layers were identified in the keloid dermis. The superficial dermis of keloid was characterized by active fibroblasts and lymphocytes; the middle dermis contained dense extracellular matrix with large numbers fibroblasts, and the deep dermis was poorly cellular and characterized by hyalinized collagen bundles. In the keloid samples, from the superficial to the deep dermis, type I collagen increased and type III collagen decreased, and fibroblasts from the superficial dermis of the keloid were found to migrate more rapidly. In conclusion, the findings of this study showed that different depths within the keloid dermis displayed different biological features. The superficial dermis may initiate keloid formation, in which layer intralesional injection of pharmaceuticals and other treatments should be performed for keloid.